LEADERSHIP COMMUNICATION STRATEGY AT THE ADMINISTRATIVE BUREAU OF THE REGIONAL SECRETARIAT OF SOUTHEAST SULAWESI PROVINCE IN IMPROVING EMPLOYEE PERFORMANCE - Safarudin, Safarudin; Razak, Abdul; Kalsum, Ummy (Penelitian dan Pengembangan Ilmu, 2024)
This study aims to evaluate and analyze the communication strategy of leaders in the Administrative Bureau of the Regional Secretariat of Southeast Sulawesi Province in improving employee performance. An effective leadership communication strategy is considered crucial in creating a productive and efficient work environment. The methodology used in this study included in-depth interviews with employees at the Adpim Bureau to obtain their views on various aspects of leadership communication, including audience introduction, message drafting, method selection, and use of communication media. The results of the study show that the leaders at the Adpim Bureau of the Provincial Secretariat. South Sulawesi is actively implementing a communication strategy that involves the use of various communication media, such as face-to-face meetings and digital messaging, to ensure the clarity of information. The leadership also emphasized the importance of direct feedback and personal interaction to improve employee understanding and performance. This study identifies that clear and structured communication contributes significantly to improving employee performance, by reducing misunderstandings and facilitating effective task delivery. The conclusion of this study confirms that the communication strategies implemented by leaders greatly affect productivity and work efficiency. This study suggests that further research be conducted to explore leadership communication styles, conflict management strategies, optimization of communication media, support for employee career development, and better performance evaluation practices. This finding is expected to provide guidance for leaders at the Adpim Bureau and similar organizations in designing more effective communication strategies to improve employee performance.